Primary Cutaneous Nocardiosis (Lymphangitic Type) in an Immunocompetent Patient: A Case Report - Hilayali Aguilar-Molina; Sonia Toussaint-Caire; Roberto Arenas; Juan Xicohtencatl-Cortes; Luary C. Martínez-Chavarría; Rigoberto Hernández-Castro; Carmen Rodriguez-Cerdeira (Microorganisms)
Cutaneous nocardiosis is an uncommon bacterial infection caused by Nocardia spp.; Nocardia brasiliensis is the agent involved in most cases. This infection is acquired through the direct traumatic inoculation of soil, plants, or other substrates where the bacteria are found. Clinically, it usually manifests as an erythematous ulcerated nodule. In one-third of cases, nodules or gummas are distributed over the lymphatic pathways that resemble lymphocutaneous sporotrichosis. Its manifestations vary and can present acutely or more frequently with a latent clinical picture over time. Diagnosis is established mainly by Gram staining, biopsy, exudate culture, and molecular biology. Nocardia infections can recur, implying that antimicrobial therapy must be prolonged (between 6 and 12 months) and involve monitoring patients for at least 6 months after the end of treatment. Early diagnosis and targeted treatment may reduce patient mortality rates. We report the case of an 82-year-old woman who presented with four nodules with a lymphangitic spread on her left hand and forearm, one week after the trauma. Molecular identification was performed using 16S rDNA gene sequencing, and Nocardia brasiliensis was identified.